EXPLORING CLASSROOM LANGUAGE IMPLEMENTED BY NOVICE ENGLISH TEACHERS AT JUNIOR HIGH SCHOOLS - Primurizki, Juliance; Suherdi, Didi (Universitas PGRI Sumatera Barat, 2023)
Using English as a classroom language is widely acknowledged as the most effective means to encourage students to get used to English. The more often they are exposed to English, the more proficient they will be. However, teachers' awareness of the role of classroom language as a means to maximize student proficiency remains vague. Studies reveal that EFL teachers tend to use their own language in the classroom rather than the target language, English. Furthermore, teachers are susceptible to code-switching, which is the use of two or more languages in a single sentence or phrase. Despite the growing attention of studies exploring classroom language used by EFL teachers, studies focusing on novice EFL teachers with less than five years of teaching experience are considered limited. Accordingly, this descriptive qualitative study aims to investigate the implementation of classroom language used by two EFL novice teachers based on Sallaberri's framework from the English Classrooms Handbook: Classroom Language (1995). The data were gathered through a questionnaire and semi-structured interviews. The study's findings revealed that two EFL novice teachers use Bahasa Indonesia as their primary classroom language, including code-switching. Besides, using English as a classroom language became teachers’ dilemma since the students' proficiency levels and their experience in teaching are strongly affected their actions. Some recommendations and potential future practices and research are also discussed thoroughly.